Potential distribution of three types of ephemeral plants under climate changes - Lan, Zhang; Huiliang, Liu; Hongxiang, Zhang; Yanfeng, Chen; Lingwei, Zhang; Kudusi, Kawushaer; Taxmamat, Dilxadam; Yuanming, Zhang (Frontiers in Plant Science, 2022)
Arid and semi-arid regions account for about 40% of the world’s land surface area, which are the most sensitive areas to climate change, leading to a dramatic expansion of the arid region in recent decades. Ephemeral plants are crucial herbaceous in this area and are very sensitive to climate change. But we are still unclear about which factors can determine the distribution of ephemeral plants, and how the distribution of ephemeral plants responds to future climate change across the global. Understanding the impact of climate change on ephemeral plant distribution is crucial for sustainable biodiversity conservation. Here, we explored the potential distribution of three types of ephemeral plants in arid and semi-arid (cold desert, hot desert and deciduous forest) on a global scale by using the MaxEnt software. We used species global occurrence data and 30 environmental factors in scientific collections. Our results showed that (1) the average value of the area under the receiver operating curve (AUC) of each species was higher than 0.95, indicating that the MaxEnt model’s simulation accuracy for each species was good. (2) Distributions of cold desert and deciduous forest species were mainly determined by soil pH and annual mean temperature; key factors determine the distribution of hot desert species was precipitation of the driest month. (3) The potential distribution of ephemeral plant in the cold desert was increased under one-third of climate scenarios; in the hot desert, the potential suitable distribution for Anastatica hierochuntica were decreased in more than half of climate scenarios, but Trigonella arabica increased in more than half of climate scenarios; in deciduous forest ephemeral plants Crocus alatavicus decreased in near nine-tenths of climate scenarios, and the Gagea filiformis increased in 75% of climate scenarios. The potential suitable distributions of ephemeral plants in the different ecosystem were closely related to their specific adaptation strategies. These results would contribute to a comprehensive understanding of the potential distribution pattern of some ephemeral plants in arid and semi-arid ecosystems.